Comparative evaluation of laparoscopic versus open appendicectomy in cases of acute appendicitis - Gupta, Atul Kumar; Chawda, Vishal; Gupta, Shalabh; Goel, Apoorv; Bhagat, Tripta S.; Agarwal, Ayush (International Surgery Journal, 2017)
Background: Conventional open appendicectomy is a common emergency surgical procedure being used for more than a century. Despite continuously increasing popularity of minimal access surgery, laparoscopic appendicectomy has not gained enough popularity. Methods: A prospective randomized study to compare laparoscopic and open appendicectomy for the treatment of appendicitis was carried out from April 2015 to October 2016. Thirty patients each were randomized to two groups. Decision to operate was taken on clinical grounds. Results: Twenty-five patients in each group were confirmed to be suffering from appendicitis. While alternative diagnosis could be established in 4 out of remaining 5 patients in laparoscopic group, in only 1 out of 5 patients from open appendicectomy definitive diagnosis for pain could be established. There was no significant difference in operative time between two groups. Patients in laparoscopic group had lesser postoperative pain scores and wound complications. They also got discharged and returned to normal activity earlier than those in open appendicectomy group. Conclusions: Laparoscopic appendicectomy has lesser postoperative morbidity and improves diagnosis in nonappendicitis patients.